Beware of an anomalous left circumflex artery when considering aortic valve or root procedures. Issue 5 (13th February 2022) - Paneitz, Dane C.; Vlahakes, Gus J.; Cameron, Duke E.; Bloom, Jordan P.
Abstract: Anomalous coronary arteries pose an additional challenge when contemplating surgical options for a patient with aortic valve or root pathology. We demonstrate the course of an anomalous retro‐aortic left circumflex coronary artery arising from the right coronary sinus in a patient with an aortic root and ascending aortic aneurysm with severe aortic regurgitation who underwent ascending aorta and aortic valve replacements.